Alcaligenes is Commensal Bacteria Habituating in the Gut-Associated Lymphoid Tissue for the Regulation of Intestinal IgA Responses - Kunisawa, Jun; Kiyono, Hiroshi (Frontiers in Immunology, 2012)
Secretory-immunoglobulin A (S-IgA) plays an important role in immunological defense in the intestine. It has been known for a long time that microbial stimulation is required for the development and maintenance of intestinal IgA production. Recent advances in genomic technology have made it possible to detect uncultivable commensal bacteria in the intestine and identify key bacteria in the regulation of innate and acquired mucosal immune responses. In this review, we focus on the immunological function of Peyer’s patches, a major gut-associated lymphoid tissue, in the induction of intestinal IgA responses and the unique immunological interaction of Peyer’s patches with commensal bacteria, especially Alcaligenes, a unique indigenous bacteria habituating inside Peyer’s patches.